2014
DOI: 10.1051/epjconf/20136900010
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Microscopic Calculations of Level Densities by the Shell Model Monte Carlo Method

Abstract: Abstract. The shell model Monte Carlo (SMMC) method enables calculations in model spaces that are many orders of magnitude larger than those that can be treated by conventional methods, and is particularly suitable for the calculation of level densities in the presence of correlations. We review recent advances and applications of SMMC for the microscopic calculation of level densities. Recent developments include (i) a method to calculate accurately the ground-state energy of an odd-mass nucleus, circumventin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Our computation of the dynamical correlation functions here relies on a new algorithm which improved the computational scaling in the calculation of imaginarytime correlation functions [40] from O(N 3 s ) in standard algorithms [41][42][43][44][45][46] to O(N s N 2 p ). The algorithm lets fluctuations related to creation/destruction operators or density/spin operators propagate in imaginary time, coupled to the stochastic evolution of the underlying AFQMC random walk or path-integral [40].…”
mentioning
confidence: 99%
“…Our computation of the dynamical correlation functions here relies on a new algorithm which improved the computational scaling in the calculation of imaginarytime correlation functions [40] from O(N 3 s ) in standard algorithms [41][42][43][44][45][46] to O(N s N 2 p ). The algorithm lets fluctuations related to creation/destruction operators or density/spin operators propagate in imaginary time, coupled to the stochastic evolution of the underlying AFQMC random walk or path-integral [40].…”
mentioning
confidence: 99%
“…Using the stochastic linear combination (24) as an approximation to the ground state | Ψ 0 we get immediately:…”
Section: Computation Of Observablesmentioning
confidence: 99%
“…There are many examples of important applications along these lines [9][10][11][12][13][14][15][16][17], with the frontier of interesting sign-problem-free situations still being actively expanded. A key class of applications with direct experimental and theoretical importance are in systems involving ultracold Fermi atoms [18][19][20][21][22][23][24][25] and more recently, in cold atom systems with spin-orbit coupling [26,27]. It was also shown that the use of a BCS trial wave function in the unitary Fermi gas can both reduce projection time (to reach the ground state) and dramatically improve the statistical accuracy of the computed ground-state energy [18].…”
Section: Introductionmentioning
confidence: 99%